2003
DOI: 10.1093/gerona/58.2.m176
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Fitness Reduces Brain Tissue Loss in Aging Humans

Abstract: These findings extend the scope of beneficial effects of aerobic exercise beyond cardiovascular health, and they suggest a strong solid biological basis for the benefits of exercise on the brain health of older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
557
5
20

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 828 publications
(625 citation statements)
references
References 18 publications
36
557
5
20
Order By: Relevance
“…Other potential mechanisms may involve more endotheliumdependent vasodilatation as a result of more NO bioavailability (Green et al 2004) and/or cerebral angiogenesis (Rhyu et al 2010;Swain et al 2003;Ding et al 2006;Black et al 1990). In support of this, ageinduced cerebral atrophy appears to be less marked in those with higher aerobic fitness (Colcombe et al 2003). Furthermore, 6 months of aerobic exercise training can even increase brain volume in previously sedentary older individuals (Colcombe et al 2006), so a corresponding increase in CBF would seem plausible.…”
Section: Introductionmentioning
confidence: 86%
“…Other potential mechanisms may involve more endotheliumdependent vasodilatation as a result of more NO bioavailability (Green et al 2004) and/or cerebral angiogenesis (Rhyu et al 2010;Swain et al 2003;Ding et al 2006;Black et al 1990). In support of this, ageinduced cerebral atrophy appears to be less marked in those with higher aerobic fitness (Colcombe et al 2003). Furthermore, 6 months of aerobic exercise training can even increase brain volume in previously sedentary older individuals (Colcombe et al 2006), so a corresponding increase in CBF would seem plausible.…”
Section: Introductionmentioning
confidence: 86%
“…68 Research on neuroimaging suggests that prefrontal and parietal circuits in the brain, the regions of the brain that are most involved in executive control, retain more plasticity. For example, in a cross-sectional study, Colcombe and colleagues 69 reported that fitter older subjects had a greater volume of gray matter in the prefrontal, parietal, and temporal regions and a greater volume of white matter in the genu of the corpus callosum than their less fit counterparts, after controlling for potential confounders.…”
Section: Physical Activity and The Prevention Of Dementia Ad Or Cogmentioning
confidence: 99%
“…It is possible that cognitive function and brain structure are cumulatively affected by individual health behavior, years of education, wealth, the ability to cope with stress, personality traits, and indicators of physical health such as body mass index (BMI) (Backman et al, 2006;Colcombe et al, 2003;Craik, 2006;Lindenberger and Baltes, 1997;Salthouse, 2003;Singh-Manoux et al, 2004;Smith, 2003;Springer et al, 2005). Therefore, we also examined the influence of psychosocial and physical health factors on cognitive and structural variables.…”
Section: Introductionmentioning
confidence: 99%